Study of the Parenthood of Mothers Victims of Conjugal Violence: How to Help? - Daria Druzhinenko-Silhan; Anne Thevenot; Claire Metz (Psicologia: Teoria e Pesquisa)
Abstract In this paper we present the first results of a research on the parenthood of mothers who are victims of conjugal violence. The main objective is to improve support for mothers. The 12-month research protocol includes clinical interviews, projective methods (genogram, CAT and TAT) and the Relation Scale Questionnaire. We present here the results obtained from 7 clinical interviews with the mothers and a case study. The results show a high level of insecurity, unstable points of reference in terms of social and psychological reality, and a deterioration in internal resources. Support for victimized mothers and their parenthood must therefore be provided not only on a socio-economic level, but also on a psychological level, to help them rebuild their lives.